Drug sensitivity and drug resistance profiles of human intrahepatic cholangiocarcinoma cell lines - Tepsiri, Nisana (World J Gastroenterol, 2005)
AIM: To study the effect of a number of chemotherapeutic drugs on five human intrahepatic cholangiocarcinoma (CCA) cell lines. The expressions of genes that have been proposed to influence the resistance of chemotherapeutic drugs including thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD), glutathione-S-transferase P1 (GSTP1), multidrug resistance protein (MDR1) and multidrug resistance-associated proteins (MRPs) were also determined. METHODS: Five human CCA cell lines (KKU-100, KKU-M055, KKU-M156, KKU-M214 and KKU-OCA17) were treated with various chemotherapeutic drugs and growth inhibition was determined by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay. Semi-quantitative levels of gene expression were determined by a reverse transcriptase polymerase chain reaction (RT-PCR). Results of IC(50) values and the ratios of gene expression were analyzed by linear regression to predict their relationship. RESULTS: Among five CCA cell lines, KKU-M055 was the most sensitive cell line towards all chemotherapeutic drugs investigated, particularly taxane derivatives with IC(50) values of 0.02-3 nmol/L, whereas KKU-100 was apparently the least sensitive cell line. When compared to other chemotherapeutic agents, doxorubicin and pirarubicin showed the lowest IC(50) values (<5 μmol/L) in all five CCA cell lines. Results from RT-PCR showed that TS, MRP1, MRP3 and GSTP1 were highly expressed in these five CCA cell lines while DPD and MRP2 were only moderately expressed. It should be noted that MDR1 expression was detected only in KKU-OCA17 cell lines. A strong correlation was only found between the level of MRP3 expression and the IC(50) values of etoposide, doxorubicin and pirarubicin (r = 0.86-0.98, P<0.05). CONCLUSION: Sensitivity to chemotherapeutic agents is not associated with the histological type of CCA. Choosing of the appropriate chemotherapeutic regimen for the treatment of CCA requires knowledge of drug sensitivity. MRP3 was correlated with resistance of CCA cell lines to etoposide, doxorubicin and pirarubicin, whereas other chemotherapeutic drugs showed no association. The role of this multidrug resistance-associated protein, MRP3, in chemotherapeutic resistance in CCA patients needs to be further investigated.